Implementasi Zero Knowledge Proof Menggunakan Protokol Feige Fiat Shamir Untuk Verifikasi Tiket Rahasia - Willy Sudiarto Raharjo; Dessy Sutanti (Ultimatics : Jurnal Teknik Informatika, 2015)
Cryptography is known for it’s ability to protect confidential information, but it can also be used for other purposes. One of them is for identity verification or authentication. One of the biggest disadvantages of traditional authencation method is at the end of the session, the verifier knows about secrets which is supposed to be known only by prover. In this paper, we implemented a ZeroKnowledge Proof-based secret ticket verification system using Feige Fiat Shamir protocol. The goal of this system is to help prover identified themselves to the verifier, but also prevent the verifier to understand anything about the prover’s secret information. The system is also able to prevent ticket duplication or double-use of tickets by using an interactive proof verification method. By combining it with cryptography, not only we can achieve completeness and soundness property of Zero-Knowledge Proof, but we can also achieve information security property. Index Terms - Feige Flat Shamir, Verification, Zero Knowledge Proof.